GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 9850 species occurrences available in GBIF matching the query: TaxonKey: Physconia distorta (With.) J. R. Laundon HasCoordinate: TRUE HasGeospatialIssue: FALSE. The dataset includes 9850 records from 92 constituent datasets: 13 records from Specimens of lichen herbarium KPABG. 5 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 4 records from BLS Lichen Database: Welsh churchyards. 13 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 64 records from HBRG Fungus, Lichen & Lower Plants Dataset. 2 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 11 records from PlutoF platform observations. 119 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 25 records from BioFokus. 881 records from Artdata. 5 records from OHN. 212 records from BLS Lichen Database: English churchyards. 22 records from Australia's Virtual Herbarium. 18 records from Estonian Museum of Natural History. 2 records from NINA botanical collection. 6 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 1 records from FFH-Gebiet "Calwer Heckengäu". 7 records from naturgucker. 4 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Lichen. 1 records from RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 1 records from National Trust - Hatfield Forest species data held by The National Trust.. 1 records from Dutch Vegetation Database (LVD). 84 records from Lichen herbarium, NTNU University Museum. 340 records from Lichen herbarium, Oslo (O). 2 records from Dorset Sites of Nature Conservation Interest (SNCI) species records 2000-2008. 5 records from IBF Monitoring of Lichens. 8 records from The Lichen Collection at the Botanische Staatssammlung München. 1 records from BIOTA Southern Africa - The Collection of Lichens at the Botanische Staatssammlung München. 66 records from Natural History Museum (London) Collection Specimens. 4 records from Ireland's BioBlitz. 68 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 75 records from Herbarium Senckenbergianum (FR) - Fungi. 2 records from Canadian Museum of Nature Herbarium. 1357 records from BLS Lichen Database: Scotland. 67 records from Real Jardin Botanico, Madrid: MA-Lichen. 17 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 5 records from Michigan State University Herbarium Lichens. 38 records from Arizona State University Lichen Collection. 1 records from Botanical Museum, Copenhagen, the Lichen Herbarium. 17 records from Danish Mycological Society, fungal records database. 93 records from Lichen Herbarium Berlin. 513 records from Biologiezentrum Linz. 63 records from LiquenCAT: Banco de datos de los líquenes de Cataluña. 9 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 5 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 2 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Verified data. 30 records from Universitat de València, Colecciones de Criptógamas: VAL_Lich. 81 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from LaBoOb02. 1 records from Danielsberg (Mölltal, Kärnten). 1 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 1 records from Gemeinde Sursee. 1 records from Schlern - (Bozen). 1 records from GEO Hauptveranstaltung Tirol (Innsbruck). 1 records from Zukünftiges NSG Höftland/Bockholmwik. 1 records from Neckartalsüdhang (Horb). 1 records from Unser Schulgelände. 1 records from Gurgltal (Tarrenz). 4 records from Lichens of North-Eastern Poland. 361 records from Natural History Museum, University of Tartu. 6 records from Lichens of Biebrza National Park. 58 records from Herbarium of Umeå University (UME). 1176 records from BLS Lichen Database: England. 1 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 99 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 1 records from Artenvielfalt am Schlern. 6 records from Lichen Collection - University of Washington Herbarium (WTU). 2082 records from BLS Mapping Scheme dataset, 1750-2009. 1 records from TransForest vegetation data. 215 records from BLS Lichen Database: Wales. 3 records from ARKO gamle edellauvtrær. 207 records from Lund Botanical Museum (LD). 1 records from National Trust - Ickworth species data held by The National Trust.. 146 records from Norwegian Species Observation Service. 13 records from Lichens of Knyszyn Forest. 26 records from Lichens from Russian Fennoscandia. 3 records from Royal Botanic Garden Edinburgh Herbarium (E). 4 records from LNHG Biological Records Dataset. 3 records from Lichen herbarium, NMBU. 2 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 5 records from Herbarium WRSL, Lichens Collection. 3 records from Lichen collection, Norwegian Forest and Landscape Institute. 528 records from Lichen field notes, Oslo (O). 1 records from Ecofact. 3 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 2 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 36 records from Lichen herbarium, Tromsø Museum. 1 records from National Trust for Scotland Species Records. 3 records from Geneva Herbarium – General Collection (G). 2 records from BRERC species records within last 15 years. 73 records from Lichen herbarium, UiB. 395 records from Fungi (S). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences